Criminality among Young People With Substance Use Problems in Sweden: A One-Year Follow-Up Study - Anderberg, Mats (Journal of drug issues, 2022)
Swedish drug policy has a strong focus on minor drug violations. This longitudinal study analyses the association between criminality and substance use problems among young people who have received outpatient treatment and risk factors that predict continued problems with criminality. Research on this target group is under development in Sweden, but there are few follow-up studies. The study indicates that about one-quarters of the young people who begin outpatient treatment have been convicted of crimes at 1-year follow-up. Most of them who had been convicted with offences also have ongoing problems with substance use and three-quarters of the young people had been charged with a drug-related offence. More than five risk factors give an elevated risk of continued criminality. Interventions meeting the needs of young people, moving away from the current emphasis on penal law principles, may also contribute to reduced criminality in this target group.